Influence of Different Indigenous Microorganisms Manure on Early Growth of Cassia alata - Amaliah, Mazlan (2018)
Indigenous microorganisms (IMOs) are considered as natural fertilizer, made up from natural occurring microbes like fungi, yeast and bacteria, collected from the surrounding environment. Their roles in contributing to soil fertility and enhancing plant growth performance are well accepted. However, there is very few information on the identification of IMOs and their effect on plant growth as well as soil physico-chemical properties have been reported. The aims of the study were to isolate and identify the IMOs and to evaluate the influence of different IMOs manure on early growth of Cassia alata and soil physico-chemical properties. The IMOs were collected from bamboo area, forest area and C. alata plant in UNIMAS. The microorganisms were isolated through serial dilution method then identified based on morphological characterization and/or molecular analysis. A total of 31, 25 and 33 microbial isolates were collected from the bamboo areas, forest areas, and C. alata plant, respectively. Aspergillus aculeatus, Trichoderma harzianum, Bacillus mycoides, Leifsonia sp, and Serratia marcescens were the most dominant IMOs found in bamboo area with percentage of 21-33 %.. While, A. nomius, Penicillium rolfsii, B. mycoides and B. cereus happened to be the most found in forest area with percentage of 18-50 %. A. aculeatus, A. nomius, F. equiseti, Lasiodiplodia pseudotheobromae, B. amyloliquefaciens, and B. cereus were dominantly found in C. alata plant with range of 17 -40 %. The effect of different IMOs manure on early growth of C. alata was conducted in UNIMAS. A randomized block design with three treatments, IMOs M1, IMOs M2, and control, were replicated three times. IMOs M1 was prepared by inoculating the IMOs from forest areas while IMOs M2 was done through mixing of lactic acid bacteria and IMOs from forest areas, bamboo areas and C. alata leaves. Four weeks of seedling with uniform height were transplanted into polybags, containing 2 kg of sterilized iv soil. Treatments 1 (IMOs M1) and 2 (IMOs M2) were added with manure, accordingly at 68 g per polybag every four weeks starting from 4th week after planting to 14th weeks. Data on plant height, stem diameter, chlorophyll content, root length, root/shoot ratio were recorded every 2 weeks starting from the 4th week after planting to 14th weeks. The IMOs M1 treated plants significantly higher in plant height and stem diameter from week 8th to the end of planting period. However, chlorophyll content of IMOs M1 treated plants having a fluctuate result but still recorded the highest content in week 6th, 34.1 ± 0.88 μmol/m2. At the end of the experiment, IMOs M1 plants also had the longest average root length, 30.05 ± 2.46 cm, but statistically no significant different to IMOs M2 plants. Soil sample were collected at depth of 0-20 cm to evaluate soil pH, total nitrogen content (TNC), organic carbon (OC), available phosphorus (AP) and exchangeable bases (K+, Ca2+, Mg2+ and Na+). The analysis was done using kjeldahl method, dry combustion method, bray no 2, and ammonium acetate extraction method. IMOs manure added soil decreased in soil pH, Ca2+ and Na+ content. However, the soil increased in TNC, OC, AP, K+, and Mg2+ content. Therefore, IMOs M1 were recommended as a better manure as it revealed a significant higher on plant growth in term of plant height, stem diameter and chlorophyll content. Besides, soil analysis revealed that IMOs M1 treated soil decreased soil pH while increased in total N, OC, AP and most of exchangeable bases such as K+ and Mg2+ as time progressed. The finding showed degradation of organic matter and mineralization of plant nutrition are all happened in the soil which then leads to a better growth of C. alata.